The Necessity of Implementation by Local Values: Historical Study of ethnics conflict in Sampit Central Kalimantan Indonesia - Didi Susanto; Sidik Puryanto (Universitas Medan Area, 2022)
This study aims to analyze ethnic conflict in Kalimantan Indonesia. As a country with Â a different culture and identity variant, the potential for conflict is very vulnerable to reappear. The research method in this study used qualitative study with historical analysis model. This method uses both primary and secondary supporting data with predominantly historical books relevant to ethnic conflict, supported by national and international journals and articles. The results of this study reveal that the historicalization of the conflict is still a grudge and each ethnic identity is still dominant in its group feeling and creates a perception of identity justification. This study conveys to the conclusion that the potential of a vulnerable Indonesian State of ethnic conflict can emerge as a time-bomb and any time due to political, economic, and norms. In order to prevent the ethnic conflict in Kalimantan from recurring, the State must be strong. The recommendations in this study adopted from the education of valuesÂ that prioritize the value of harmony, the value of togetherness, in adapting to understand and implement the real philosophical in life is